Parenting stress, psychological well-being, and perceived social support of teenage mothers. - Gonzales, Julio Joseph Dingle
This study assessed the parenting stress, psychological well-being and perceived social support of teenage mothers. The study also explored the relationship between these variables. Thirty (30) teenage mothers from La Castellana, Negros Occidental and Miagao, Iloilo served as respondents of the study. The results showed that teenage mothers experience moderately low levels of parenting stress, have minimally high psychological well-being and have moderately high levels of perceived social support. The study also found a significant positive correlation between perceived social support and psychological well-being while parenting stress is negatively correlated with psychological well-being. However, perceived social support is not associated with parenting stress.